Chitooligosaccharides promote diabetic wound healing by mediating fibroblast proliferation and migration - Zihan Li; Chuwei Zhang; Lei Wang; Qingrong Zhang; Yipeng Dong; Xinyu Sha; Bolin Wang; Zhihan Zhu; Wenmiao Wang; Yongjun Wang; Youlang Zhou; Yi Zhang (Scientific Reports)
Abstract Diabetic wounds are notoriously difficult to heal due to impaired cell repair mechanisms, reduced angiogenesis, and a heightened risk of infection. Fibroblasts play a vital role in wound healing by producing extracellular matrix (ECM) components and various growth factors, but their function is inhibited in diabetic wounds. Chitooligosaccharides (COS), intermediate products of chitosan degradation, have shown efficacy in promoting tissue repair, yet their role in diabetic wound healing remains underexplored. In a mouse model of diabetic wounds, COS treatment demonstrated substantial bioactivity in accelerating wound healing by enhancing fibroblast proliferation and migration. Additionally, COS increased collagen III deposition and angiogenesis at the wound sites. The COS also mitigated inflammatory responses by controlling leukocyte infiltration and bacterial infection. Mechanistically, COS regulated fibroblast activity via the PI3K/Akt signaling pathway, providing a novel bioactive material for chronic wound healing.